2011
DOI: 10.1259/bjr/55980445
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector CT imaging of pleura: comparison of two contrast infusion protocols

Abstract: Objectives: Imaging of the pleura by multidetector CT (MDCT) can be challenging. There is no clear evidence or guidelines on contrast infusion parameters for imaging pleura. We compared two contrast protocols for assessing pleural pathology on MDCT.Methods: This was a prospective study in which consecutive patients with MDCT for suspected pleural disease on chest radiograph were randomised into two groups. The first group received 150 ml of intravenous contrast at a rate of 2.5 ml s -1 and the second group rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 20 publications
3
24
0
2
Order By: Relevance
“…In our study, we found that MDCT was sensitive in diagnosing all cases of pleural lesions, and this result was in accordance with Raj et al [14] who stated that MDCT allows detailed evaluation of the pleura and differentiation of benign from malignant pleural disease. Adequate enhancement of the pleura enables differentiation of the thickened pleura from adjacent effusion or aerated or collapsed lung.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found that MDCT was sensitive in diagnosing all cases of pleural lesions, and this result was in accordance with Raj et al [14] who stated that MDCT allows detailed evaluation of the pleura and differentiation of benign from malignant pleural disease. Adequate enhancement of the pleura enables differentiation of the thickened pleura from adjacent effusion or aerated or collapsed lung.…”
Section: Discussionsupporting
confidence: 91%
“…However the primary objective of this study was to assess the incidence of pulmonary emboli [7] and the diagnostic performance of CTPA for PM was not reported. In a small randomised study, Raj et al previously demonstrated better enhancement of the pleura utilising delayed phase (at 60–90 s post-contrast) CT acquisition [8], Therefore venous-phase CT should be requested in all patients with suspected PM, and this may have been used more frequently in the Hallifax study. Our study clearly demonstrates that this approach is frequently not taken in a more generalizable population and may be even less frequently used than reported here, since our centres did have a stated interest in pleural disease and were recruiting to DIAPHRAGM.…”
Section: Discussionmentioning
confidence: 99%
“…However, this could be further improved by altering some of the imaging parameters, such as kV, without significantly reducing scan quality. Some units have developed scan protocols with prolonged contrast bolus injections that allow intermediate vessel enhancement and good quality pleural imaging [17] in a single scan acquisition, thereby minimizing radiation. However, pulmonary artery opacification is not as high as with formal CTPA, and thus, PE could be potentially overlooked.…”
Section: Discussionmentioning
confidence: 99%